IMPLEMENTATION ANALYTICAL HIERARCHY PROCESS AND WEIGHTED PRODUCT METHOD FOR LOVEBIRD SELECTION IDENTIFICATION APPLICATIONS - Yolanda Nur Oktavia; Nurhayati Nurhayati; Iskandar Fitri (Jurnal Riset Informatika, 2021)
Among the many types of birds in Indonesia, lovebirds are pets that attract the most attention and become a favorite among the public. This is evidenced by the many communities of lovebird lovers throughout Indonesia. The problem that exists for ordinary people who do not understand the animal world and have little knowledge about the quality of the lovebirds, it is not uncommon for the problem to be in doing business for sellers it is difficult to make decisions in overcoming the problem of selecting the best birds. Based on this problem, the author compares the combination of the analytical hierarchy process and weighted product methods with the analytical hierarchy process and TOPSIS from this comparison, the highest score is 392.63 on the analytical hierarchy process and weighted product for the best quality web-based lovebird selection recommendation application design application. From the results of application testing and manual calculations with 64 sample data, it was concluded that 4 users or about 6% were included in the low accuracy category in the best lovebird recommendation results, 12 users or 19% of the total tests were stated at a moderate level of accuracy in the lovebird recommendation results. The best and 48 users or 75% of the total tests were stated at the high accuracy category level in the best lovebird recommendation results with the highest accuracy value of 80.2% on the Albino lovebird type.